Huddling alleviates the decrease in glycogen and lipid content in the liver of Brandt’s vole caused by mild cold environment - Jin-Hui Xu; Lu-Fan Li; Xiao-Lu Zhang; Xiao-Tong Kong; Xing-Chen Wang; Li-Na Jiang; Zhe Wang (Zoologia (Curitiba))
ABSTRACT Low/cold ambient temperatures can induce hepatic damage in mammals, prompting the evolution of huddling as an adaptive strategy among small mammals to survive cold conditions in the wild. However, the specific mechanisms by which low/cold ambient temperatures and huddling influence the liver remain poorly characterized. This study examined the impact of huddling on liver glycogen and lipid metabolism in wild Brandt’s vole, Lasiopodomys brandtii (Radde, 1861) under low/cold ambient conditions. Results indicated that: (1) Compared to the Control group (CON), the Resting Metabolic Rate of the Cool separated group (CS) increased, whereas the Cool huddling group (CH) exhibited no change; (2) Liver glycogen content decreased, and glycogen phosphorylase activity increased in both the CH and CS groups compared to the CON group. However, CH showed a less pronounced reduction in glycogen content and attenuated glycogen phosphorylase hyperactivity compared to CS. Glycogen synthase activity remained consistent across all groups; (3) Compared with the CON group, the CS group exhibited decreased triglyceride content, fatty acid synthase activity, and acetyl-coenzyme A carboxylase activity. Conversely, triglyceride content and fatty acid synthase activity in CH were unchanged, while acetyl-coenzyme A carboxylase activity was higher compared to CS. Hepatic lipase activity was stable across all experimental groups. These results indicate that low/cold ambient temperatures decrease hepatic glycogen and lipid reserves in the livers of Brandt’s voles. However, huddling mitigates these effects by inhibiting glycogen breakdown and promoting lipid synthesis, thereby enhancing physiological resilience to cold stress.